Bersama orang tua atau tidak? Melihat hubungan antara dukungan sosial teman sebaya dengan penyesuaian diri mahasiswa tahun pertama ditinjau dari status tempat tinggal - Riztiardhana, Dimas; Prameswari, Annisa Diyah; Warni, Weni Endahing (Jurnal Psikologi Poseidon, 2025)
Adaptation is a process through which individuals adjust to new environments, including first-year college students who must navigate an educational system that differs substantially from high school. This study aimed to examine whether residential status moderates the relationship between peer social support and adjustment among first-year college students. A moderation correlational design was employed using a survey method for data collection. A total of 194 first-year students at Hang Tuah University participated in the study through a saturated sampling technique. The instruments used were the Self-Adjustment Scale and the Peer Social Support Scale, both developed by the researcher, with a reliability coefficient of 0.887. Analysis using PROCESS Model 1 indicated that residential status did not moderate the relationship between peer social support and adjustment. This finding suggests that whether students live with their parents or not does not significantly alter the strength of the relationship between peer social support and adjustment in first-year college students.